Formalized approaches to assessing the usability of the user interface of web applications - B.M M. Basok; S. L. Frenkel (Российский технологический журнал, 2021)
The paper proposes an approach based on the use of mathematical methods for modeling the behavior of the designed web application and user behavior. This approach allows an evaluation of the usability of this application. The paper discusses the models of user interfaces (UI), which are used to assess the convenience of site navigation. The possibility of using two classes of UI models is shown – structural-logical (ontological) and probabilistic. Models of the first class are used to assess the degree of comprehensibility of the proposed UI navigation on the search web resource in the accepted terms. For this, mathematically defined measures of similarity between the elements of the UI and their relationships and the elements of a hypothetical (but plausible) model of the user’s perception of the search area in a given subject area are used. In particular, the paper substantiates the possibility of using Jaccard and Levenshtein lexicographic distance metrics as such measures of similarity. Probabilistic models are based on Markov chains. With the help of these models, in the presence of reliable statistical data collected during the trial operation of a web application or its prototype, it is proposed to estimate the average number of user steps required to solve a specific problem of finding information about a subject area object. The paper provides some recommendations on the use of similarity measures to improve the usability of the UI of web applications. In addition, data on the technique for estimating the probabilities of transitions of Markov chains and semantic connections are presented. To clarify the features of the UI analysis models proposed in the article, the website of the RTU MIREA Admission Committee (https://priem.mirea.ru) is provided with a fairly simple organization that provides a search for information about admission and training at the University. The application of the approach described in the paper, along with traditional methods of testing the usability of UI, will increase the overall level of usability of applications, and thereby reduce the cost of identifying and correcting related errors.